A Clinical Review on Paroxetine and Emerging Therapies for the Treatment of Vasomotor Symptoms - David PS; Smith TL; Nordhues HC; Kling JM (Dove Medical Press, 2022)
Paru S David,1 Taryn L Smith,2 Hannah C Nordhues,3 Juliana M Kling1 1Department of Internal Medicine, Mayo Clinic, Scottsdale, AZ, USA; 2Department of Internal Medicine, Mayo Clinic, Jacksonville, FL, USA; 3Department of Internal Medicine, Mayo Clinic, Rochester, MN, USACorrespondence: Paru S David, Email david.paru@mayo.eduAbstract: Most women experience vasomotor symptoms (VMS) during their menopausal transition. Menopausal hormone therapy (HT) is the most effective treatment for VMS, but some women choose not to use HT or have contraindications to using HT. Non-hormonal treatment options should be offered to these symptomatic menopausal women. Multiple large randomized controlled trials have demonstrated statistically significant reductions in hot flash severity and/or frequency with the use of selective serotonin reuptake inhibitors (SSRIs) and serotonin norepinephrine reuptake inhibitors (SNRIs). To date, paroxetine mesylate remains the only non-hormonal treatment that has been approved by the United States Food and Drug Administration (FDA) for the management of moderate to severe postmenopausal vasomotor symptoms. Lower doses are needed to reduce VMS than those used to treat anxiety or depression, which is beneficial since side effects are typically dose dependent. The recommended dosage is 7.5 mg once daily at bedtime. Dose dependent side effects include nausea, fatigue, and dizziness. Knowing potential medication interactions is critical such as with medications that can lead to serotonin syndrome, concomitant use with monoamine oxidase inhibitors and being aware of p450 drug metabolism is essential for patients taking drugs that utilize the CYP2D6 enzyme for metabolism including tamoxifen. This review discusses in detail the available data supporting the use of paroxetine for the treatment of VMS, including side effects and considerations regarding prescribing. A discussion of other emerging treatments is included as well, including estetrol, oxybutynin and neurokinin 3 (NK3) receptor antagonists.Keywords: menopause, vasomotor symptoms, non-hormonal treatments, paroxetine